KUAT TEKAN BATA MERAH DENGAN VARIASI USIA DAN KADAR AIR ADUKAN TANAH LIAT - Elhusna Elhusna; Rina Agustin (Inersia: Jurnal Teknik Sipil, 2019)
Clay mortar storage during the molding of brick often takes place in brick home industry factories. The storage caused by the time and the labors limitation. This article is the report of the research of the age of the clay mortar storage during the process of the brick. Clay mortar in this research was made at the same time and molded to be 20 bricks every day till the fith day of the clay mortarstorage. Water content of each clay mortar variations were measured. The brick production process were done as the way they did at a factory in Pasar Pedati, Midle Bengkulu Regency. The brick compressive strength test was done according to SNI 03-4164-1996 using the compression machine hand operated of 250 kN capacity. The test was done on the seventh day after the mortar covering on top and bottom of the brick. Every first crack was occurred at the brick. The strength which report is the strength of the brick when the first crack occur during the test. The two days clay mortar storage produce best compressive strength of the brick. It also has the highest clay mortar water content. The clay mortar storage of 2 untill 4 days produce bricks with better strength.